The Correlation of Smoking and Coffee Consumption with Diabetic Foot Ulcer Using Wifi Criteria at Cut Meutia General Hospital, Lhokseumawe - Syafruddin, Syafruddin; Suhartono, Raden; Sanyoto, Dhanasari Vidiawati (Indonesian Journal of Multidisciplinary Science, 2025)
Diabetic Foot Ulcer (DFU) is a serious complication of diabetes mellitus. Risk factors such as smoking habits and coffee consumption have been associated with poor glucose control and vascular dysfunction; however, their relationship to the severity of DFU is not yet fully understood. The severity of DFU wounds can be assessed using the clinically validated WIFI system (Wound, Ischemia, and Foot Infection). This research aims to evaluate the association between smoking habits and coffee consumption with the severity of DFU based on the WIFI score in patients at RSUD Cut Meutia, Aceh. This was a cross-sectional study involving 188 DFU patients who met the inclusion criteria. Statistical analysis was performed using the Chi-square test of independence. Results show a significant association was found between moderate smoking and DFU severity (p=0.002). Coffee consumption was not significantly associated with the severity of DFU (p=0.468). In multivariate analysis, no significant effect of smoking or coffee consumption on WIFI scores was found when analyzed simultaneously (p>0.05). Moderate smoking is associated with increased DFU severity, especially when combined with light or moderate coffee consumption. Coffee consumption alone did not show a meaningful relationship. The multivariate analysis did not reveal a significant simultaneous effect of both variables, suggesting the potential influence of other confounding factors on DFU severity.